(3CSGdjH GdHMK GdYdej aj GdYdhe GdELJeGYjI hGdEfSGfjIs - (3ZQGjHI(B, (3ahRjs; (3fYjes ((3YeGfs (3OGQ hGFd ddfTQ hGdJhRjYs, 2002)
(3eONd aj GdHMK GdYdej(B- (3eQGMd GdHMK GdYdej(B- (3hSGFd LeY GdHjGfGJ(B- (3WQb YQV GdHjGfGJ(B- (3JMdjd GdHjGfGJ GdEMUGFjI(B.s
Keywords: (3GdHMK GdYdejs; (3GdYdhe GdELJeGYjIs; (3GdYdhe GdEfSGfjIs